THE EFFECT OF COVID-19 TEST CANCELLATION ON HEALTH CARE WORKERS ' REMUNERATION - Martha Debora Korompis; Marjes Netro Tumurang; Sandra Gerce Jelly Tombokan; Atik Purwandari; Frederika Nancy Losu; Sjenni Olga Tuju; Syaifoel Hardy (International Journal of Social Science, 2022)
The signs of a drastic decline in Covid-19 cases will have an impact on various related businesses where healthcare workers are involved. With the end of the Covid-19 pandemic, it will automatically result in the abolition of the PCR or Antigen Test which will have an impact on the reducing of their remuneration. The purpose of this study is to analyze the impact of canceling the Covid-19 test on several types of remuneration for health workers. This study used PRISMA analysis supported by the PICOT model. The research was conducted through document search, keyword identification and article review from Google Scholar (n=41), SagePub (n=16), Pubmed (n=6), Semantic Scholar (n=4), and others (n= 31). Other documents were discarded because they were irrelevant, duplication, and other reasons that were not on topic (n=29). The results of the PRISMA analysis showedfour problems faced by health workers as a result of the reduction in Covid-19 tests for health workers, namely: a decrease in job vacancies, a reduction in functional benefits and a decrease in personal business for health workers. We recommended to the empowerment of COVID-19 health workers and increasing business potential for health workers as an effort to restore the welfare of health workers.